A caryophyllene oxide and other potential anticholinesterase and anticancer agent in Salvia verticillata subsp. amasiaca (Freyn & Bornm.) Bornm. (Lamiaceae). Issue 6 (1st November 2020) - Karakaya, Songul; Yilmaz, Serdar Volkan; Özdemir, Özlem; Koca, Mehmet; Pınar, Nur Münevver; Demirci, Betül; Yıldırım, Kadir; Sytar, Oksana; Turkez, Hasan; Baser, K. Hüsnü Can
ABSTRACT: In vitro cholinesterase inhibition, antioxidant and anticancer potentials of the essential oils and extracts of flowers and aerial parts of Salvia verticillata subsp. amasiaca have been studied. The GC-MS and GC-FID analyses found that major components of the essential oils were caryophyllene oxide, caryophylladienol II, spathulenol, hexahydrofarnesyl acetone and phytol. Oxygenated sesquiterpenes and sesquiterpene hydrocarbons were identified in the essential oils as the dominating groups of compounds. Caryophyllene oxide indicated strong cholinesterase inhibitory activities and antioxidant effect. The essential oil from aerial parts exhibited high anticancer activity on U-87 MG and PC-3 cells with 0% and 45.56% cell viability, respectively. Microscopic analysis of different parts of the experimental plant revealed that glandular trichomes of flowers contain more oxygenated sesquiterpene hydrocarbons, while glandular trichomes of the aerial parts contain monoterpene hydrocarbons. It was confirmed that S. verticillata subsp. amasiaca had similar kinds of capitate and peltate trichomes like other Salvia members.